TRAINING ON IMPLEMENTATION OF DIRECT SELLING MARKET USING QRIS DIGITAL PAYMENT FOR STRAWBERRY FARMERS AND SELLERS IN BERASTAGI, KARO REGENCY, SUMATERA NORTH - Jihan Hidayah Putri; Dewi Sundari Tanjung; Suriana; Winda Wardhani; Rodi Syafrizal; Iqbal Fahri Tobing (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
Karo Regency, particularly Berastagi District, is one of the largest strawberry production centers in North Sumatra. To date, most strawberry farmers and sellers still rely on conventional sales systems through middlemen and cash transactions, resulting in relatively small profit margins and inefficient transaction processes. This community service activity aims to provide training on implementing a direct selling market (direct sales without intermediaries) combined with the use of the QRIS (Quick Response Code Indonesian Standard) digital payment system to strawberry farmers and sellers in Berastagi. The implementation method included a preliminary survey, focus group discussions (FGDs), theoretical and practical training, assistance with QRIS account registration, and an evaluation of the program's sustainability. The results showed that participants experienced an increased understanding of the concept of direct selling and the benefits of cashless payments, marked by the successful QRIS registration by most participants and increased buyer confidence, especially tourists, in cashless transactions at sales locations. This activity is expected to serve as a model for replication for other horticultural centers in efforts to digitize the rural economy.